Науково-методичні підходи у формуванні підготовчого процесу в контексті трансформації залізничного транспорту - Олійник, Г.Ю. (Економічні інновації, 2012)
Розглядаються науково-методичні підходи до формування підготовчого процесу, щодо реструктуризації підприємств залізничного транспорту. In this article scientific and methodological approaches are considered when forming a preparatory process for restructuring of railway transport enterprises.
The offered approaches (the restructuring preparation technique) will ensure the forecast of a business development, reduce probability of losses because of making groundless or ill-timed strategic decisions including scarcity financing.